The recent emergence of a highly related virulent Clostridium difficile clade with unique characteristics. (April 2020) - Shaw, H.A.; Preston, M.D.; Vendrik, K.E.W.; Cairns, M.D.; Browne, H.P.; Stabler, R.A.; Crobach, M.J.T.; Corver, J.; Pituch, H.; Ingebretsen, A.; Pirmohamed, M.; Faulds-Pain, A.; et al.
Abstract: Objectives: Clostridium difficile is a major global human pathogen divided into five clades, of which clade 3 is the least characterized and consists predominantly of PCR ribotype (RT) 023 strains. Our aim was to analyse and characterize this clade. Methods: In this cohort study the clinical presentation of C. difficile RT023 infections was analysed in comparison with known 'hypervirulent' and non-hypervirulent strains, using data from the Netherlands national C. difficile surveillance programme. European RT023 strains of diverse origin were collected and whole-genome sequenced to determine the genetic similarity between isolates. Distinctive features were investigated and characterized. Results: Clinical presentation of C. difficile RT023 infections show severe infections akin to those seen with 'hypervirulent' strains from clades 2 (RT027) and 5 (RT078) (35%, 29% and 27% severe CDI, respectively), particularly with significantly more bloody diarrhoea than RT078 and non-hypervirulent strains (RT023 8%, other RTs 4%, p 0.036). The full genome sequence of strain CD305 is presented as a robust reference. Phylogenetic comparison of CD305 and a further 79 previously uncharacterized European RT023 strains of diverse origin revealed minor genetic divergence with >99.8% pairwise identity between strains. Analyses revealed distinctive features among clade 3 strains, including conserved pathogenicity locus, binary toxin and phage insertion toxin genotypes, glycosylation of S-layer proteins, presence of the RT078 four-gene trehalose cluster and an esculinase-negative genotype. Conclusions: Given their recent emergence, virulence and genomic characteristics, the surveillance of clade 3 strains should be more highly prioritized.